Celebrating ten years of ISME's Revista Internacional de Educación Musical : Music education research in Ibero-America - Serrano, Rosa M.; López-Íñiguez, Guadalupe; Aróstegui, José Luis (Routledge, 2025)
This chapter discusses the importance of music education research and its democratisation around the world, highlighting the importance of reaching all countries with possibilities to research and publish their quality research and to access and apply it in music education. This is the philosophy with which the ISME’s Revista Internacional de Educación Musical (RIEM) was born ten years ago. It should be noted that Spanish is one of the most widely spoken languages in the world and the mother tongue in many countries while, at the same time, there are very little quality fora to publish research in this field. This is why this journal makes its use possible, both for researchers and music educators who are carrying out quality research that should be disseminated and for all those potential readers who feel more confident in this language. In the same way, the commitment to open access publication seeks to democratise knowledge, allowing all those areas with fewer economic resources to use it. ISME’s firm commitment to the democratisation and universalisation of knowledge and research in music education goes one step further with this book, bringing this quality research to the English-speaking public as well. In this paper we will discuss all these issues and the role the RIEM journal has played during its ten years of existence.
Keywords: musiikkikasvatus; Latinalainen Amerikka; musiikintutkimus